Психология женщины в выборе партнера - Островерхова, Е. А. (ХНУРЭ, 2012)
The given work is devoted to the modern women’s problems of their choice of sexual partner. Sexual differentiation is one of the important problems in studying social psychological processes and phenomena in various application fields of social psychology. Addressing the relationship of opposite sexes is very important nowadays, because it is a solution, and marital conflict, key to the preservation of marriage. There are many theories associated with this problem, and their study is interesting, though not uniquely.